Improving Students Speaking Ability with English Song - agung purnama; Imam Wahyudi Karimullah (International Journal Labs, 2024)
Language impacts the daily lives of members of any race, creed, and region of the world. Especially in Indonesia, beside Bahasa Indonesia, most the people using English as a part of their education. The use of songs can facilitate the students in more interesting learning activities because learners can get a different learning experience when it can be implemented by teachers effectively. The songs also can analyze the many issues in the lyrics, such as love, hatred, and revenge, and therefore practice speaking by expressing their thoughts and views on the songs' contents. The research carried out is descriptive qualitative, the data in the research collected was information about children's speaking abilities with English songs. Research data was collected from various sources including informants or sources, namely teachers and students. Based on the processed data that the author has described in the discussion; it can be concluded that using songs to improve English language skills is an effective way because songs are easy to find in students' lives. Apart from that, songs are also easy for students to understand and memorize. Using songs can help students develop their listening and pronunciation skills, which can also increase their vocabulary.